2022
DOI: 10.1172/jci.insight.155145
|View full text |Cite
|
Sign up to set email alerts
|

Limited induction of SARS-CoV-2–specific T cell responses in children with multisystem inflammatory syndrome compared with COVID-19

Abstract: Why Multisystem Inflammatory Syndrome in Children (MIS-C) develops after SARS-CoV-2 infection in a subset of children is unknown. We hypothesized that aberrant virusspecific T-cell responses contribute to MIS-C pathogenesis. We quantified SARS-CoV-2 reactive T-cells, serologic responses against major viral proteins, and cytokine responses from plasma and peripheral blood mononuclear cells in children with convalescent COVID-19, acute MIS-C, and healthy controls. Children with MIS-C had significantly lower viru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 41 publications
2
19
0
Order By: Relevance
“…T cell receptor repertoire analyses have led to the hypothesis that the SARS-CoV-2 spike protein has a superantigen effect, causing T cell dysregulation that contributes to the development of MIS-C 15 . Finally, flow cytometry analyses have demonstrated that children with MIS-C have reduced virus-specific CD4+ and CD8+ T cells compared to children with COVID-19 and controls 16 .…”
Section: Introductionmentioning
confidence: 99%
“…T cell receptor repertoire analyses have led to the hypothesis that the SARS-CoV-2 spike protein has a superantigen effect, causing T cell dysregulation that contributes to the development of MIS-C 15 . Finally, flow cytometry analyses have demonstrated that children with MIS-C have reduced virus-specific CD4+ and CD8+ T cells compared to children with COVID-19 and controls 16 .…”
Section: Introductionmentioning
confidence: 99%
“…In brief, PBMCs were seeded in duplicate in 96-well plates (2x10 5 cells/well) and stimulated for 48 h with pools of SARS-CoV-2 S protein peptides or N protein peptides (2 μg/ml per peptide, see Supplementary Table S2 ). The T cell peptides used in this study were identified by sequence homology and by a priori epitope prediction using bioinformatics approaches to identify potential targets for immune responses to the SARS-CoV-2 ( 23 ), and it has been widely recognized ( 24 26 ). An anti-CD3 monoclonal antibody (mAb) was used as a positive control, and RPMI 1640 medium was used as a negative control.…”
Section: Methodsmentioning
confidence: 99%
“…There is conflicting evidence regarding the functional capacity of the antibody responses in children, while some studies reported neutralizing antibody responses of lower magnitude in children, 43,44 other studies observed comparable plasma antibody responses and neutralizing antibody titers in children and adults. 45,46 Several studies have documented that SARS-CoV-2-specific T cell responses are reduced in children compared with adults. 46,47 Both the frequencies of CD4 + and CD8 + T cell responses to SARS-CoV-2 structural and ORF1ab proteins are lower in infants compared with adults when IFNγ production or T cell activation are assessed, and infants also have lower frequencies of effector memory CD4 + T cells.…”
Section: Robus T Immunit Y To Sar S -Cov-2 Infec Ti On and Vaccinati ...mentioning
confidence: 99%
“…47 T cell responses persist and increase with time post infection in both age groups. 47 The impact on disease severity on T cell responses requires further clarification as both reduced 46 and stronger 48 Pediatric immunity to SARS-CoV-2 mRNA-LNP vaccination has also proven to be robust, as demonstrated in the Pfizer and Moderna mRNA-LNP dosing studies in children ages 5-11 where vaccine doses of half or less than that used in adults were able to achieve similar spike-specific IgG responses and neutralizing titers. 49,50 Moreover, pre-fusion stabilized Spike mRNA-LNP vaccination of 2 month-old nonhuman primates at a lower dose than studied in pre-clinical adult nonhuman primate vaccines achieved high magnitude and durable binding and neutralizing antibody responses.…”
Section: Robus T Immunit Y To Sar S -Cov-2 Infec Ti On and Vaccinati ...mentioning
confidence: 99%
See 1 more Smart Citation